2019
DOI: 10.4414/smw.2019.20072
|View full text |Cite
|
Sign up to set email alerts
|

Behçet’s syndrome: clinical presentation and prevalence in Switzerland

Abstract: OBJECTIVE: Behçet's syndrome is a rare systemic autoimmune/autoinflammatory disease affecting mucocutaneous tissues, the skin and the eyes, as well as the joints, the central nervous system, the gastrointestinal tract and blood vessels. Because of the lack of clinical data in Switzerland, the aims of this cohort study were to calculate the disease prevalence and to analyse the disease manifestations and the immune-suppressive medication. METHODS: Data were extracted from 52 patient charts. Thereafter, all pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…4a) while only low seismicity is observed. This observation appears to be surprising although it is not the first time that extension was constrained across the Jura arc: the same conclusion was reached after mapping the strain field of Switzerland using 3D interpolation of strain rates on a regular grid 77 ; and after a joint processing of the AGNES/COGEAR datasets 78 . The extension is therefore not due to an artefact of network geometry or an interpolation issue.…”
Section: Resultsmentioning
confidence: 75%
“…4a) while only low seismicity is observed. This observation appears to be surprising although it is not the first time that extension was constrained across the Jura arc: the same conclusion was reached after mapping the strain field of Switzerland using 3D interpolation of strain rates on a regular grid 77 ; and after a joint processing of the AGNES/COGEAR datasets 78 . The extension is therefore not due to an artefact of network geometry or an interpolation issue.…”
Section: Resultsmentioning
confidence: 75%
“…Although contrary to other global reports with a low prevalence of disease, this finding may be supported by the awareness of BD among treating physicians in the region. For instance, an eight-year delay between symptom onset and the diagnosis was reported in Switzerland [17].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the low prevalence of BS, most physicians in low prevalence countries are unfamiliar with the disease and its differentials: Studies in Germany, the Netherlands or Switzerland have demonstrated a diagnostic delay of up to 8 years from disease onset to time of diagnosis (17). In addition, clinicians falsely invoke fulfilment of the above-mentioned diagnostic/classification criteria as well as HLA-B51 positivity when establishing the diagnosis of BS (10).…”
Section: Introductionmentioning
confidence: 99%